Why are open ascending auctions popular? The role of information aggregation and behavioral biases - Theo Offerman; Giorgia Romagnoli; Andreas Ziegler (Tinbergen Institute, 2020)
The popularity of open ascending auctions is often attributed to the fact that openly observable bidding allows to aggregate dispersed information. Another reason behind the frequent utilization of open auction formats may be that they activate revenue enhancing biases. In an experiment, we compare three auctions that differ in how much information is revealed and in the potential activation of behavioral biases: (i) the ascending Vickrey auction, a closed format; and two open formats, (ii) the Japanese-English auction and (iii) the Oral Outcry auction. Even though bidders react to information conveyed in others' bids, information aggregation fails in both open formats. In contrast, the Oral Outcry raises higher revenue than the other two formats, by stimulating bidders to submit unprofitable jump bids and triggering a quasi-endowment effect.
Keywords: C90; D44; D82; 330; ascending auctions; information aggregation; jump bidding; auction fever